Mucopolysaccharidosis in children as seen through the eyes of an ophthalmologist - Grałek, Mirosława; Niwald, Anna; Piasecka, Katarzyna (Klinika Oczna / Acta Ophthalmologica Polonica, 2025)
Mucopolysaccharidosis is a rare, genetically determined metabolic disease. It arises from abnormalities related to the absence or deficiency of lysosomal enzymes needed to break down glycosaminoglycans. Glycosaminoglycans are involved in the metabolic processes of living organisms. Disturbances in lysosomal metabolism causes their accumulation in body tissues and organs, accompanied by pathological symptoms including characteristic general and visual changes. There is no causal (genetic) therapy for mucopolysaccharidosis. Treatment is exclusively symptomatic. Available therapeutic modalities include enzyme replacement therapy and bone marrow transplantation. Ophthalmological treatment comprises correction of refractive errors and other conservative and surgical methods aimed to improve the ocular condition.